Serological and Molecular Characterization of the Hepatitis B Virus in Blood Donors in Maputo City, Mozambique - Olga Maquessene; Osvaldo Laurindo; Lúcia Chambal; Nalia Ismael; Nédio Mabunda (Viruses)
Hepatitis B virus (HBV) is a major public health concern responsible for hepatitis and hepatocellular carcinoma (HCC) worldwide. In Mozambique, HBsAg prevalence is high and endemic, and despite the strategies to mitigate the spread of the disease, the HCC incidence is still high and one of the highest in the world. There is still limited data on the serological profile and molecular epidemiology of HBV in Mozambique given the burden of this disease. In this study, we aimed to describe the serological and molecular characterization of HBV among blood donors. We conducted a cross-sectional survey from November 2014 to October 2015 at the Blood Bank of the Hospital Central de Maputo. Serological testing and molecular testing were performed. The frequency of HBV infection was estimated at 4.4% and was higher among males (79.1%), individuals aged 25–39 years (55.2%), and replacement donors (89.6%). The median viral load of HBV-positive blood donors was 1288.5 IU/mL, and 43.8% had a viral load higher than 2000 IU/mL. Most of the sequenced samples (94.3%) belonged to subgenotype A1. These findings underscore the importance of ongoing surveillance to inform effective HBV control strategies and present evidence about the burden of HBV among blood donors, which definitely requires attention, and clinical blood banks in Mozambique and in similar settings.